Content validity and testretest reliability with principal component analysis of the translated Malay four-item version of Paffenbarger physical activity questionnaire - Fazlisham Ghazali (Tanjong Malim, 2020)
Content validity and testretest reliability with principal component analysis of the translated Malay four-item version of Paffenbarger physical activity questionnaire by Fazlisham Ghazali